Detection of Motif in Protein Sequence Using K-Means and Fuzzy C-Means Algorithms - Geethamani, R; Kalaivani, B (International Journal of Computer Sciences and Engineering, 2025)
Finding the Motif in biological sequences of protein synthesis is a basic problem in determining the protein structure. Detection of the Motif is used with many applications in gene regulation, protein family identification and determination of functionally and structurally important identities. Large amount of biological data is used to resolve the problem of discovering patterns in biological sequences computationally. In this research, we have designed an approach using a system of clustering in data mining to detect frequently occurring informative motifs that are high in information content. We have proposed a comparative approach for Skin Melanin associated problems(SMA) detection in preliminary stages using protein sequence. We have used the protein sequence with normal and abnormal data as the trained dataset. Test instances are classified into normal to abnormal by comparing it with the fundamental dataset. In this paper, We compare and evaluate the performance of two clustering algorithms namely K-means and fuzzy c-means clustering for protein sequences